2008
DOI: 10.1002/j.0022-0337.2008.72.2.tb04461.x
|View full text |Cite
|
Sign up to set email alerts
|

Realigning Biomedical Science Instruction in Predoctoral Curricula: A Proposal for Change

Abstract: Currently in North America, there is an active dialogue going on about the state of predoctoral dental education and the need for curriculum change, innovation, and the adoption of contemporary, competency-based educational models. At the institutional level, curriculum committees struggle with requests from faculty to add new content to an overburdened didactic and clinic schedule. This article will describe potential solutions centering on the role and scope of the biomedical sciences in predoctoral dental e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Lack of time to engage in eLearning activities due to high teaching workload is a recurring concern reported in the literature. Increasing overcrowding of the curriculum due to, among other factors, the inclusion of new biomedical knowledge and clinical procedures also restricts educator ability to train in eLearning activities 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Lack of time to engage in eLearning activities due to high teaching workload is a recurring concern reported in the literature. Increasing overcrowding of the curriculum due to, among other factors, the inclusion of new biomedical knowledge and clinical procedures also restricts educator ability to train in eLearning activities 24 .…”
Section: Discussionmentioning
confidence: 99%
“…However, that study also found that the completion of undergraduate science courses did not significantly impact student performance indicators in dental school. Others have reasoned that basic science courses should be integrated with clinical courses 3 . The Commission on Dental Accreditation (CODA) standard 2–14 mandates that “Graduates must be competent in the application of biomedical science knowledge in the delivery of patient care.” 4 However, the very nature of national examinations, in which NBDE Part I occurs between the basic science and clinical coursework, solidifies the division between basic science and clinical professors.…”
mentioning
confidence: 99%
“…We believe our results here support this conclusion. Previous studies have looked at undergraduate prerequisites and changes to some admission's requirements have been made [30,31]. Such trends may be identifiable at individual institutions and support transitioning to using such tools rather than test scores.…”
Section: Discussionmentioning
confidence: 99%